The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1002/1097-0142(19920201)69:3<839::aid-cncr2820690336>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Gestational and nongestational trophoblastic tumors distinguished by DNA analysis

Abstract: In three patients in whom a diagnosis of gestational trophoblastic tumor was possible on the basis of pathology and elevated levels of serum human chorionic gonadotrophin, locus‐specific minisatellite probes were used to identify restriction fragment length polymorphisms (RFLP) in DNA from the tumor, the patient, and her partner. On the basis of results from these studies, one tumor, originally diagnosed as a germ cell tumor, was reclassified as a gestational choriocarcinoma, whereas a second tumor, diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 24 publications
0
53
0
1
Order By: Relevance
“…Choriocarcinomas of gestational and non-gestational origin have a distinct prognosis, but cannot be distinguished by routine histological examination (22). Molecular genetic analysis may reliably identify the genetic origin of a pure ovarian choriocarcinoma (23)(24)(25); however, as this is an unestablished and costly technique with limited availability, it was not used it in this case. However, our patient was in the high-risk group of endometrial cancer due to the lymph node metastasis and the histological type, i.e., undifferentiated carcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…Choriocarcinomas of gestational and non-gestational origin have a distinct prognosis, but cannot be distinguished by routine histological examination (22). Molecular genetic analysis may reliably identify the genetic origin of a pure ovarian choriocarcinoma (23)(24)(25); however, as this is an unestablished and costly technique with limited availability, it was not used it in this case. However, our patient was in the high-risk group of endometrial cancer due to the lymph node metastasis and the histological type, i.e., undifferentiated carcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of other germ cell elements is indicative of germ cell choriocarcinoma. Choriocarcinoma of gestational origin can be established by identification of paternal component with the help of DNA analysis which is a reliable method for identifying the genetic origin of pure ovarian choriocarcinomas 10,13,14,15 . However, since such techniques are always expensive and not generally available in our institution,, the application is limited.…”
Section: Discussionmentioning
confidence: 99%
“…1981: Chaganti et al. 1990Fisher et al, 1992) or from a pregnancy with complete hydatidiform mole which is androgenetic, having only a paternal contribution to the nuclear genome (Fisher et al, 1988;Fisher et al. 1992).…”
Section: Resnismentioning
confidence: 99%
“…Genetic studies have confirmed the origin of choriocarcinoma from normal term pregnancy or homozygous or heterozygous complete hydatidiform moles (Fisher et al, 1988;Chaganti et al, 1990;Fisher et al, 1992), but have also shown that the causative pregnancy in trophoblastic tumours is not always the antecedent pregnancy (Fisher et al, 1992). Thus a clinical diagnosis of post-term or post-mole PSTT is not conclusive evidence of the origin of the tumour.…”
mentioning
confidence: 99%